1995
DOI: 10.1007/bf02049149
|View full text |Cite
|
Sign up to set email alerts
|

Sucrase-isomaltase is an independent prognostic marker for colorectal carcinoma

Abstract: These results indicate that SI is a prognostic marker for CRC that is independent of stage-related variables in patients who have undergone potentially curative resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
0
18
0
2
Order By: Relevance
“…We have previously shown that expression of SI in primary colorectal carcinomas is associated with a nearly twofold increase in the recurrence of that cancer at a distant site (19). In the present work we assessed first whether the expression of the phenotypic markers SI, DF3, or galectin 3 was significantly associated with standard clinical or pathologic variables or with each other in a set of 165 patients who underwent surgery between 1965 and 1977.…”
Section: Association Of Pbenotypic Marker Expression With Standard CLmentioning
confidence: 98%
See 4 more Smart Citations
“…We have previously shown that expression of SI in primary colorectal carcinomas is associated with a nearly twofold increase in the recurrence of that cancer at a distant site (19). In the present work we assessed first whether the expression of the phenotypic markers SI, DF3, or galectin 3 was significantly associated with standard clinical or pathologic variables or with each other in a set of 165 patients who underwent surgery between 1965 and 1977.…”
Section: Association Of Pbenotypic Marker Expression With Standard CLmentioning
confidence: 98%
“…2). When a multivariate Cox proportional hazards analysis was performed, neither DF3 nor galectin 3 were significant covariates when included in the final model that retained SI (19). The sample size and follow-up duration were adequate to rule out a 50% difference in survival with at least 80% power and 5% type I error for a two-sided hypothesis test of equal hazard ratios for the marker being present versus absent.…”
Section: Df3 and Galectin 3 Are Not Prognostic Markersmentioning
confidence: 99%
See 3 more Smart Citations